Applied superconductivity - Wolsky, A. M.; Thomas, R. A. (Noyes Data Corp., 1989)
Discusses the impact of recent superconducting materials research, indicating research goals which appear realistic and, if reached, would enable diverse commercial applications of the new materials.
Keywords: Superconductors.; Superconductors -- Industrial applications.; elektronické knihy; electronic books